2015
DOI: 10.1080/19393210.2015.1074945
|View full text |Cite
|
Sign up to set email alerts
|

Ochratoxin A in dried grapes in Hamadan province, Iran

Abstract: The occurrence of ochratoxin A (OTA) in dried grapes was surveyed in this study. Sixty-six samples of dried grapes (40 currants, 16 sultanas and 10 raisins) were collected from dried grapes factories in Hamadan province, Iran, from October 2012 to March 2013. High-performance liquid chromatography (HPLC) was used to determine OTA in these samples. OTA was detected in 23 (57.5%) currants, 10 (62.5%) sultanas and 6 (60%) raisins samples. Levels in five samples exceeded the Institute of Standards and Industrial R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 27 publications
(27 reference statements)
1
13
0
Order By: Relevance
“…; Coronel et al . , Heshmati and Mozafarinegad ). The European Commission has determined maximum permitted OTA limits of 3µg/kg in bread (European Commission ).…”
Section: Introductionmentioning
confidence: 97%
“…; Coronel et al . , Heshmati and Mozafarinegad ). The European Commission has determined maximum permitted OTA limits of 3µg/kg in bread (European Commission ).…”
Section: Introductionmentioning
confidence: 97%
“…Ochratoxin A (OTA) is the secondary metabolite of Aspergillus strains and penicillium (Heshmati & Mozaffari Nejad, ; Mansouri‐Nasrabadi, Milani, & Nazari, ; Valle‐Algarra et al, ). OTA has been classified as human carcinogenic, in the Group 2B, by the IARC (IARC, ).…”
Section: Introductionmentioning
confidence: 99%
“…OTA has been classified as human carcinogenic, in the Group 2B, by the IARC (IARC, ). Previous studies have shown that OTA is nephrotoxic mycotoxin with carcinogenic, immunotoxic, mutagenic, and neurotoxic properties (Heshmati & Mozaffari Nejad, ; Heshmati, Zohrevand, Khaneghah, Nejad, & Sant’Ana, ).…”
Section: Introductionmentioning
confidence: 99%
“…OTA was eluted from the column by passing 1.5 ml of HPLC-grade methanol/acetic acid (98: 2, v/v). Then, 20 μl of eluate was injected into the HPLC (Heshmati & Mozaffari Nejad, 2015).…”
Section: Extraction Of Otamentioning
confidence: 99%